Analisis Kualitas Produk Botol 30ml Dengan Parameter Temperatur Pada Mesin Injection Molding Model Blow - Elapri, Bima Yoel; Ramdan, Dadan; Umroh, Bobby (Jurnal Ilmiah Teknik Mesin & Industri (JITMI), 2023)
Injection molding is one method that is widely used because of the lower cost required. The resulting plastic product is inseparable from the problem of product defects. This research uses quantitative methods and data collection or field on the subject of research, after that analyzing each parameter. The results of this study the occurrence of several defects in the product, namely short molding product defects have the most defects, namely 3, while over mold, sink mark and weldmark or flow product defects are 2 and the least is the hole product defect, namely 1. The setting at temperature determines the quality, especially in terms of appearance, at a temperature of 190 0C gives a much better product quality compared to temperatures of 180 and 200 0C. Analyze the optimal screw speed of 8 Rpm so that the resulting product can become a desired bottle product. Analysis of product defects that occur are Sink Mark, Weldmark or flow mark, Shrinkage and Over Mold which occurs at temperatures of 180 - 200 0C. The defects that most often arise because the mold has uneven lines so that defects occur in bottle products.